2012
DOI: 10.6061/clinics/2012(07)06
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and predictors of symptomatic intracranial hemorrhage after intravenous thrombolysis for acute ischemic stroke in a Brazilian public hospital

Abstract: OBJECTIVE:Scarce data are available on the occurrence of symptomatic intracranial hemorrhage related to intravenous thrombolysis for acute stroke in South America. We aimed to address the frequency and clinical predictors of symptomatic intracranial hemorrhage after stroke thrombolysis at our tertiary emergency unit in Brazil.METHOD:We reviewed the clinical and radiological data of 117 consecutive acute ischemic stroke patients treated with intravenous thrombolysis in our hospital between May 2001 and April 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
2
4
0
2
Order By: Relevance
“…However, according to recent data from the Get With the Guidelines-Stroke Program, of the acute IS patients treated with tPA within 3 h of symptom onset, fewer than one third had door-to-needle times of ≤60 min [ 38 ]. Our thrombolysis times, which did not change after extension of the tPA time to 4.5 h, were similar to two other national cohorts [ 39 , 40 ] as well as the last SITS-ISTR [ 36 ].…”
Section: Discussionsupporting
confidence: 85%
“…However, according to recent data from the Get With the Guidelines-Stroke Program, of the acute IS patients treated with tPA within 3 h of symptom onset, fewer than one third had door-to-needle times of ≤60 min [ 38 ]. Our thrombolysis times, which did not change after extension of the tPA time to 4.5 h, were similar to two other national cohorts [ 39 , 40 ] as well as the last SITS-ISTR [ 36 ].…”
Section: Discussionsupporting
confidence: 85%
“…Patients with symptomatic hemorrhagic transformation obtained NIHSS scores higher than 15 points on admission, with statistical significance (p<0.01), corroborating the data presented in the literature. (15,21) When compared with the literature, (8,18) this study found a higher percentage of patients with 15 points or more on the NIHSS. The percentage fell after thrombolytic treatment, dropping from 56% to 12.5%, a statistically significant difference (p<0.01).…”
Section: Discussionmentioning
confidence: 51%
“…(26) Frequency of symptomatic hemorrhagic transformation was greater in comparison to other studies. Al-Khaled et al (20) found 6%; Tong et al, (15) 5%; Tosta et al (7) and Cougo-Pinto et al (21) found a frequency of 6%. The higher frequency of hemorrhagic transformation in this study can be explained by higher NIHSS scores and the presence of comorbidities such as atrial fibrillation and heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, a metanálise com dados individuais de pacientes de Whiteley et al (2016) mostrou que, embora o melhor desfecho do tratamento com trombolítico esteja associado ao menor intervalo possível entre o aparecimento de sintomas e a administração (assim como à gravidade do evento), a probabilidade de um desfecho ótimo a partir do tratamento no intervalo de 4,5 horas excede o risco de morte. No Brasil, um estudo com pacientes de AVCi grave [escore mediano na escala NIHSS = 16 (10-20)] que receberam trombólise intravenosa em um hospital público até 4,5 horas após o início dos sinais e sintomas de fato não relatou aumento na ocorrência de HIC (Cougo-Pinto et al, 2012). Além disso, um estudo realizado em hospital no estado de Roraima mostrou que, em pacientes sem A R$ 13.000,00 R$ 8.000,00 R$18.000,00 R$28.000,00 R$33.000,00 R$38.000,00 R$43.000,00 tratamento trombolítico (Ribeiro Fonseca et al, 2018), o AVCi teve um impacto significativo quanto ao desfecho socioeconômico: na amostra de 50 pacientes adultos, 10 pacientes recebiam benefícios/seguros governamentais antes do AVCi; depois de seis meses do AVCi, esse número subiu para 31.…”
Section: Discussionunclassified
“…Foram utilizados parâmetros distintos, de acordo com o tempo até o tratamento (0-3 h ou 3-4,5 h), para o grupo que recebeu trombólise. Assim, o resultado agrupado para o braço trombólise é ponderado pela proporção de pacientes tratados em cada período, conforme descrito em coorte de pacientes atendidos em hospital público do Brasil, onde, entre pacientes tratados em 0-4,5 h, 50,5% foram tratados em até 3 h e 49,5% foram tratados em 3-4,5 h (Cougo-Pinto et al, 2012).…”
Section: Desenho Do Modelounclassified